Comparing the Drought Tolerance of Local Rice Cultivar Superwin with Other Cultivars Cultivated in North Sulawesi Province Based on Dry Matter Partitioning - Ai, Nio Song; Ludong, Daniel Peter Mantilen (Proceeding International Conference on Global Resource Conservation, 2013)
This study evaluated the drought tolerance in local rice cultivar Superwin and some other rice cultivars that are cultivated in North Sulawesi based on the dry matter partitioning. This study aimed to compare the drought tolerance of the local rice cultivar Superwin with other cultivars that are cultivated in North Sulawesi Province and to examine morphological characters that are able to be used as the indicators of drought tolerance in rice. The experiment was conducted in the glasshouse using 6 rice cultivars (cv. Superwin, Sultan, Ciherang, Serayu, Cigeulis and IR 64) grown in the soil mixture at the vegetative stage. The treatments in this experiment were water deficit (without water for 4 weeks) and well-watered (watering until field capacity). The morphological characters consisted of root dry mass, shoot dry mass, total biomass, root: shoot ratio. Root: shoot ratio was a potential indicator for drought-tolerance in rice and Superwin was potential as a drought-tolerant rice cultivar.Â Keywords: glasshouse, morphological characters,Â vegetative, water deficit